Identification of the biosynthetic gene clusters for the lipopeptides fusaristatin A and W493 B in Fusarium graminearum and F. pseudograminearum - Sørensen, J.; Sondergaard, T.; Covarelli, Lorenzo; Fuertes, P.; Hansen, F.; Frandsen, R.; Saei, W.; Lukassen, M.; Wimmer, R.; Nielsen, K.; Gardiner, D.; Giese, H. (American Chemical Society and American Society of Pharmacognosy, 2014)
© 2014 The American Chemical Society and American Society of Pharmacognosy. The closely related species Fusarium graminearum and Fusarium pseudograminearum differ in that each contains a gene cluster with a polyketide synthase (PKS) and a nonribosomal peptide synthetase (NRPS) that is not present in the other species. To identify their products, we deleted PKS6 and NRPS7 in F. graminearum and NRPS32 in F. pseudograminearum. By comparing the secondary metabolite profiles of the strains we identified the resulting product in F. graminearum as fusaristatin A, and as W493 A and B in F. pseudograminearum. These lipopeptides have previously been isolated from unidentified Fusarium species. On the basis of genes in the putative gene clusters we propose a model for biosynthesis where the polyketide product is shuttled to the NPRS via a CoA ligase and a thioesterase in F. pseudograminearum. In F. graminearum the polyketide is proposed to be directly assimilated by the NRPS.